1986
DOI: 10.1042/bj2360359
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation-state-dependent ATP-binding site of cytochrome c. A possible physiological significance

Abstract: Cytochrome c binds certain physiological anions that are known to modulate the biological properties of the protein, although it is not known whether this effect is fortuitous or has physiological significance. We have examined the ability of the protein and its semisynthetic analogues to associate with certain of these anions, e.g. ATP, ADP, Pi and citrate. Our results show that specific residues or clusters of residues on the surface of horse heart cytochrome c are involved in the recognition sites for these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…Secondly, the substrate pressure in the respiratory chain, and thus the ferro/ferricytochrome c ratio, affects mitochondrial respiration. This substrate control is further modulated by anions, in particular by the concentrations of ADP and ATP, which also bind to cytochrome c (Corthesy and Wallace, 1986) and modulate the rate of electron transfer from ferrocytochrome c to cytochrome-c oxidase (Craig and Wallace, 1995). Thirdly, the concentration of oxygen affects mitochondrial respiration, and fourthly, the matrix ATP/ADP ratio, as described in the present paper, results in allosteric feedback inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the substrate pressure in the respiratory chain, and thus the ferro/ferricytochrome c ratio, affects mitochondrial respiration. This substrate control is further modulated by anions, in particular by the concentrations of ADP and ATP, which also bind to cytochrome c (Corthesy and Wallace, 1986) and modulate the rate of electron transfer from ferrocytochrome c to cytochrome-c oxidase (Craig and Wallace, 1995). Thirdly, the concentration of oxygen affects mitochondrial respiration, and fourthly, the matrix ATP/ADP ratio, as described in the present paper, results in allosteric feedback inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A high affinity binding site for ATP has been described and shown to involve the invariant Arg 91 (5,(7)(8)(9)(10). The involvement of Arg 91 in binding of ATP and consequent modulation of electron transfer by the protein has been investigated previously by semisynthetic analogs of cyt c in which this single arginine residue of the 66 -104 peptide was chemically modified by cyclohexane-1,2-dione prior to ligation with the 1-65 peptide (10).…”
Section: Discussionmentioning
confidence: 99%
“…these effects are due to nucleotide binding to cyt c or to cyt c oxidase, or both remains unclear as both cyt c and cyt c oxidase have been shown to contain at least one nucleotide-binding site (5,6). In cyt c part of the high affinity ATP-binding site is constituted by the invariant Arg 91 (5,(7)(8)(9)(10), and binding of ATP to this decreases the rate of electron flow through the mitochondrial electron transport chain (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, gel filtration and equilibrium dialysis have indicated that ferroand ferricytochrome c bind two and three molecules of ATP, respectively, at low ionic strength (11,12), and both forms bind one at higher, closer to physiological, ionic strength (13). The binding of ATP is tighter than ADP.…”
mentioning
confidence: 99%